Euthanasia, Abortion, Death Penalty and Religion - The Right to Life and its Limitations: International Empirical Research - Ziebertz, Hans-Georg; Zaccaria, Francesco (Religion and Human Rights, 2019)
This book considers how the termination of life might be accepted in the view of a general obligation to protect life. It features more than 10 papers written by scholars from 14 countries that offer international comparative empirical research. Inside, readers will find case studies from such areas as: India, Chile, Germany, Italy, England, Palestine, Lithuania, Nigeria, and Poland. The papers focus on three limitations of the right to life: the death penalty, abortion, and euthanasia. The contributors explore how young people understand and evaluate the right to life and its limitations. The book presents unique empirical research among today's youth and reveals that, among other concepts, religiosity matters. It provides insight into the acceptance, perception, and legitimation of human rights by people from different religious and cultural backgrounds. This investigation rigorously tests for inter-individual differences regarding political and judicial rights on religious grounds, while controlling for other characteristics. It will help readers better understand the many facets of this fundamental, yet controversial, philosophical question. The volume will be of interest to students, researchers, as well as general readers searching for answers